Use of sulfur binder in asphalt and cement concrete mixtures in the construction of airfields - Krayushkina, Kateryna; Lapenko, Oleksandr (International Conference “Environmental Engineering”, 2023)
Currently, work on the creation and production of new composite materials capable of long-term operation in industrial, climatic and other types of aggressive environments is one of the main tasks of the airfield industry. When organizing the production of new building materials in the context of rising prices for raw materials and energy resources, it is necessary to study the possibility of replacing the traditional raw material component with cheaper, more common raw materials, while simultaneously increasing the durability of airfield construction. One of these materials is technical sulfur. The organization of the production of sulfur-containing composites – sulfur asphalt concrete and sulfur concrete will ensure the production of new materials characterized by reduced energy consumption and ensuring reliable operation in conditions of variable temperatures and aggressive environments without increasing their cost compared to traditionally used materials. A significant reduction in excess sulfur will have a positive impact on the environmental situation in the areas of its production, a significant reduction in greenhouse gas emissions in the production of sulfur composites compared to the production of existing analogues based on traditional materials.